Catalytic manganese oxide nanostructures for the reverse water gas shift reaction. Issue 35 (28th August 2019) - He, Yulian; Yang, Ke R.; Yu, Ziwei; Fishman, Zachary S.; Achola, Laura A.; Tobin, Zachary M.; Heinlein, Jake A.; Hu, Shu; Suib, Steven L.; Batista, Victor S.; Pfefferle, Lisa D.
Abstract : We develop efficient synthetic methods to prepare various MnO2 structures and investigate their structure–property relationships as applied to the reverse Water Gas Shift (rWGS) reaction with a combination of experimental and theoretical tools. Abstract : Understanding the fundamental structure–property relationships of nanomaterials is critical for many catalytic applications as they comprise of the catalyst designing principles. Here, we develop efficient synthetic methods to prepare various MnO2 structures and investigate their catalytic performance as applied to the reverse Water Gas Shift (rWGS) reaction. We show that the support-free MnO derived from MnO2 1D, 2D and 3D nanostructures are highly selective (100% CO2 to CO), thermally stable catalysts (850 °C) and differently effective in the rWGS. Up to 50% conversion is observed, with a H2 /CO2 feed-in ratio of 1 : 1. From both experiments and DFT calculations, we find the MnO2 morphology plays a critical role in governing the catalytic behaviors since it affects the predominant facets exposed under reaction conditions as well as the intercalation of K + as a structural building block, substantially affecting the gas-solid interactions. The relative adsorption energy of reactant (CO2 ) and product (CO), Δ E = E ads (CO2 ) − E ads (CO), is found to correlate linearly with the catalytic activity, implying a structure–function relationship. The strong correlation found between E ads (CO2 ) − E ads (CO), or more generally, E ads (R) − E ads (P), and catalytic activity makes Δ E a useful descriptor for characterization of efficient catalysts involving gas-solid interactions beyond the rWGS.